The Propositional Logic of Avicenna - Avicenna. author. aut Link
XIII, 300 p.
Keywords: The main purpose of this work is to provide an English translation of and commentary on a recently published Arabic text dealing with con ditional propositions and syllogisms. The text is that of A vicenna (Abu represents his views on the subject as they were held throughout his life.